An intracellular redox sensor for reactive oxygen species at the M3‐M4 linker of GABAAρ1 receptors. (May 2014) - Beltrán González, Andrea N; Gasulla, Javier; Calvo, Daniel J
<x xml:space="preserve">Abstract</x> Background and Purpose Reactive oxygen species (ROS) are normally involved in cell oxidative stress but also play a role as cellular messengers in redox signalling; for example, modulating the activity of neurotransmitter receptors and ion channels. However, the direct actions of ROS on GABAA receptors were not previously demonstrated. In the present work, we studied the effects of ROS on GABAAρ1 receptor function. Experimental Approach GABAAρ1 receptors were expressed in oocytes and GABA‐evoked responses electrophysiologically recorded in the presence or absence of ROS. Chemical protection of cysteines by selective sulfhydryl reagents and site‐directed mutagenesis studies were used to identify protein residues involved in ROS actions. Key Results GABAAρ1 receptor‐mediated responses were significantly enhanced in a concentration‐dependent and reversible manner by H2O2. Potentiating effects were attenuated by a free radical scavenger, lipoic acid or an inhibitor of the Fenton reaction, deferoxamine. Each ρ1 subunit contains only three cysteine residues, two extracellular at the Cys‐loop (C177 and C191) and one intracellular (C364) at the M3‐M4 linker. Mutant GABAAρ1 receptors in which C364 was exchanged by alanine were completely insensitive to modulation, implying that this site, rather than a cysteine in the Cys‐loop, is essential for ROS modulation. Conclusion and Implications Our results show that the function of GABAAρ1 receptors is enhanced by ROS and that the intracellular C364 is the sensor for ROS actions.